Microscopic Analysis of Gastrointestinal Tumors: A Retrospective Study from Misurata Medical Center, Libya - Khadija Slik,; Wesam Elsaghayer,; Abdalhalim Suaiee, (AlQalam Journal of Medical and Applied Sciences, 2025)
Microscopic diagnosis of gastrointestinal biopsies remains a challenge in surgical pathology, involving both neoplastic and non-neoplastic changes. This study aims to analyze the prevalence, histopathological features, and grading of gastrointestinal (GIT) tumors in biopsies collected over 12.5 years at Misurata Medical Center, Libya, while assessing demographic patterns and the correlation of Helicobacter pylori infection with gastric malignancies. A total of 753 GIT biopsies were retrospectively analyzed from 1995 to 2007. Clinical data, including age, sex, and microscopic diagnoses, were documented. Biopsies underwent histopathological evaluation using the World Health Organization (WHO) classification. Statistical analyses were performed using SPSS software to explore relationships between neoplastic lesions and demographic factors. Non-neoplastic diseases accounted for 559 cases, which constitute 74.24% of the total cases, while neoplastic lesions were identified in 194 cases (25.76%). with a statistically significant predominance of malignant tumors (68.6%) over benign ones (31.4%, p<0.001). A slight male predominance was observed in overall biopsies (52.2%), with the 61-70 age group showing the highest frequency (17.4%). Well-differentiated tumors were more common, correlating with better prognoses. The TNM staging analysis revealed a concerning trend toward late-stage diagnoses, particularly in stomach and colorectal cancers. The investigation into Helicobacter pylori positivity indicated a complex relationship with gastric malignancies, warranting further research. The findings reflect a high burden of GIT malignancies during the study period, with late-stage diagnosis and limited diagnostic resources. These results underscore the need for improved screening programs, early detection efforts, and enhanced diagnostic infrastructure in Libya. The study underscores the importance of understanding the multifactorial influences of Helicobacter pylori in gastric cancer development.